Makna Spiritual Tradisi Pindapata Sebagai Wujud Sanghadana dalam Masyarakat Agama Buddha di Kota Magelang - Agus Subandi (Center of Language and Cultural Studies, 2021)
Pindapata is a noble custom since the time of the Buddha by walking to the people's settlements to receive food offerings from the devotees. This study aims to describe the form of the pindapata tradition as a form of sanghadana in the Buddhist community and to analyze the spiritual meaning of the pindapata tradition as a form of sanghadana in the Buddhist community. This study aims to describe the form of the pindapata tradition as a form of sanghadana in the Buddhist community and to analyze the spiritual meaning of the pindapata tradition as a form of sanghadana in the Buddhist community. This study uses a qualitative study approach using a case study model. The research was limited to one place in the Chinatown area of ​​Magelang City, Magelang Regency. The results showed that the form of the pindapata tradition as a form of sanghadana in the Buddhist community is a form of devotion for a student to the teacher and amisa dana. The spiritual meaning of the pindapata tradition as a form of sanghadana in Buddhist society is a form of gratitude by means of budi or in other words, katannukatavedi.